2001
DOI: 10.1001/archneur.58.6.905
|View full text |Cite
|
Sign up to set email alerts
|

Response to Levodopa Treatment in Dopa-Responsive Dystonia

Abstract: This pilot study suggests that retained dopamine storage in DRD may prolong the short-duration response and blur the distinction of the short- and long-duration responses. The decline in motor function in DRD on withdrawal of long-term levodopa therapy resembles that in Parkinson disease, suggesting that a long-duration response, if it exists in DRD, is unrelated to dopamine storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Furthermore, in a recent PET study it has been shown that PD patients with dyskinesias have reduced DA transporter expression, supporting the role of presynaptic alterations in the appearance of dyskinesias (27). Finally, clinical observations from DOPA-responsive dystonia show that, despite the fact that these patients have similar levels of striatal DA depletion, dyskinesias do not occur even after long-term (essentially life-long) L-DOPA treatment (28,29). As these patients do not develop DA neurodegeneration, it appears that under conditions when the presynaptic DA compartment is structurally intact, dysplastic changes in the postsynaptic striatal neurons do not lead to development of motor complications.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, in a recent PET study it has been shown that PD patients with dyskinesias have reduced DA transporter expression, supporting the role of presynaptic alterations in the appearance of dyskinesias (27). Finally, clinical observations from DOPA-responsive dystonia show that, despite the fact that these patients have similar levels of striatal DA depletion, dyskinesias do not occur even after long-term (essentially life-long) L-DOPA treatment (28,29). As these patients do not develop DA neurodegeneration, it appears that under conditions when the presynaptic DA compartment is structurally intact, dysplastic changes in the postsynaptic striatal neurons do not lead to development of motor complications.…”
Section: Discussionmentioning
confidence: 92%
“…19 Segawa disease is successfully treated with levodopa and the symptoms come back several days after the cessation of levodopa. 20 To exclude the effects of levodopa, we studied our patients 18 to 32 hours after withdrawal from levodopa because these were the longest off period which the patients could tolerate, although a complete washout of levodopa would have required 1 week or more. One article 21 showed abnormal SICI after 1 day cessation of levodopa in Segawa disease.…”
Section: Discussionmentioning
confidence: 99%
“…An initial response in a few days can be observed with small doses of levodopa. The presence of chorea and dyskinesias when the levodopa dose is increased in an attempt to obtain a response is indicative of cases that are refractory to therapy 30,35,36 . DRD patients rarely develop motor fluctuations and dyskinesias 36 .…”
Section: Dyt5 Dystoniamentioning
confidence: 99%